"Eucalyptol: An Alternative Green Solvent for the Michael Addition of Indoles to α, β‐Unsaturated Ketones and Nitrostyrenes". Issue 25 (1st July 2022) - Dave, Alpa Y.; Mishra, Akanksha; Talukdar, Mrinal; Begari, Eeshwaraiah
Abstract: Reduction of carbon footprint generated by organic solvents via replacing them with greener solvents is of great interest in recent times. Herein, we report a Michael addition reaction of indoles to α, β‐unsaturated ketones, and nitrostyrene using reusable and low toxic eucalyptol as a green solvent, and Fe(OTs)3 ⋅ 6H2 O as green catalyst. This methodology offers broad substrate scope and excellent yields (up to 90 %) in short reaction times. Abstract : Herein, we report protocol for the synthesis of 3‐alkylated indole derivatives using eucalyptol as an eco‐friendly, reusable, and sustainable bio‐solvent along with Fe(OTs)3 ⋅ 6H2 O as green catalyst for the first time. Diverse chalcones and b‐nitrostyrenes underwent Michael addition reaction with indoles to give corresponding 3‐substituted indole derivatives. This method offers excellent substrate scope (24 examples) and yields (up to 90 %) in short reaction times and recyclable, low‐toxic eucalyptol as a green alternative bio‐solvent to replace the traditional fossil fuel‐based solvents.